2018
DOI: 10.1080/15384047.2018.1529095
|View full text |Cite
|
Sign up to set email alerts
|

Ixazomib promotes CHOP-dependent DR5 induction and apoptosis in colorectal cancer cells

Abstract: Background: Ixazomib (Ninlaro), a novel proteasome inhibitor, has been developed for the treatment of many cancers and has demonstrated anti-tumor efficacy against various malignancies. However, the mechanism of the anti-tumor effect of ixazomib in colorectal cancer (CRC) cells remains unclear. Methods: MTS and flow cytometry were performed to determine the effect of ixazomib on CRC cells. Western blotting and real-time RT-PCR were performed to detect ixazomib-induced DR5 upregulation. ChIP was performed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Therefore, inducing ubiquitinated protein accumulation has become an increasingly important treatment strategy in cancer therapy, proteasome inhibitors have been reported to have significant antitumor activity against various cancer cells through this mechanism (Sato et al, 2012;Sato et al, 2014;Sato et al, 2017). The novel orally proteasome inhibitor ixazomib is currently used for treatment of multiple myeloma patients, and it has been confirmed to have killing efficiency to tumor cells (Sato et al, 2017;Yue and Sun, 2019;Harris et al, 2020). In this study, we explore whether proteasome inhibitor ixazomib have therapeutic effects on ESCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, inducing ubiquitinated protein accumulation has become an increasingly important treatment strategy in cancer therapy, proteasome inhibitors have been reported to have significant antitumor activity against various cancer cells through this mechanism (Sato et al, 2012;Sato et al, 2014;Sato et al, 2017). The novel orally proteasome inhibitor ixazomib is currently used for treatment of multiple myeloma patients, and it has been confirmed to have killing efficiency to tumor cells (Sato et al, 2017;Yue and Sun, 2019;Harris et al, 2020). In this study, we explore whether proteasome inhibitor ixazomib have therapeutic effects on ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Other scholars also reported that c-Myc was a prime transcription factor to transactivate NOXA (Nikiforov et al, 2007). A series of studies have shown that proteasome inhibitor bortezomib can induce c-Myc-dependent up-regulation of NOXA, leading to apoptosis in colorectal and pancreatic cancer cells (Yue and Sun, 2019;Lankes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding provides a clue for developing TRAIL‐sensitizing agents. Many ROS inducers, such as thapsigargin, [ 37 ] proteasome inhibitors (MG132 and ninlaro), [ 38 ] and phytocompounds [ 39 ] were reported to exhibit anticancer effects in combination with TRAIL. However, their stability and safety for the clinical application remain to be the obstacle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the appropriative level of ER stress defines a time window for adaptation and unmitigated ER stress commits the cells to an apoptosis fate. C/EBP homologous protein (CHOP) is considered to be a critical marker of ER stress‐medicated switch from pro survival to pro apoptosis, largely because of as an inducer of death receptor 5 (DR5) transcription 25,26 …”
Section: Introductionmentioning
confidence: 99%